gsimcli - Ribeiro, Sara (2019)
Ribeiro, S., Caineta, J., Costa, A. C., & Henriques, R. (2017). gsimcli: A geostatistical procedure for the homogenisation of climatic time series. International Journal Of Climatology, 37(8), 3452-3467. https://doi.org/10.1002/joc.4929